The incidence of coliform mastitis caused by E.coli - Murad, Hazhaow Omar Muhammed (The Iraqi Journal of Veterinary Medicine, 2008)
Dairy project of private sector was selected to find out the incidence ofmastitis due to E.coli or other pathogen .This dairy project was under badmanagemental feeding, housing and health practices. This dairy project wasincluded 80 cows ,thirty two cows were at milking period while the other 48were dry .Milk samples from the teats of each milking cow was collected to findout the infected quarters or udder with mastitis either by E.coli or othermicroorganism using nutrient agar ,eosin methylene blue agar and MacConkyagar then using the biochemical test as completed tests .The result revealed thattwenty six cows out of thirty two were shown positive result with mastitis.E.coli infection was highly designated (65.38 %).Single infected quartersshowed high infection rate .Anterior right and posterior left quarters recordedhigher infection rate than other quarters. Single infection of the anterior rightquarter manifested among other single infected quarters .E.coli was notspecialized in any quarter.